2001
DOI: 10.4049/jimmunol.167.12.6924
|View full text |Cite
|
Sign up to set email alerts
|

NFκB and Sp1 Elements Are Necessary for Maximal Transcription of Toll-like Receptor 2 Induced byMycobacterium avium

Abstract: We have previously reported that Toll-like receptor (TLR) 2 mRNA was induced after infection with Mycobacterium avium. To investigate the molecular basis of TLR2 expression in macrophages, we cloned and analyzed the murine putative 5′-proximal promoter. Transient transfection of a 326-bp region from nucleotides −294-+32 relative to the first transcription start site was sufficient to induce maximal luciferase activity at the basal level and after infection with M. avium in J774A.1 cells. Sequence analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 50 publications
6
71
1
Order By: Relevance
“…For example, the human TLR2 gene is constitutively expressed in monocytes and is not inducible by microbial pathogens. In contrast, the mouse TLR2 gene, which has NF-B and STAT5 transcription factor binding sites in its proximal promoter, is rapidly induced by microbial stimuli (57). The human TLR3 gene is constitutively and selectively expressed in myeloid DCs, whereas the mouse TLR3 gene is inducible and expressed in macrophages.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, the human TLR2 gene is constitutively expressed in monocytes and is not inducible by microbial pathogens. In contrast, the mouse TLR2 gene, which has NF-B and STAT5 transcription factor binding sites in its proximal promoter, is rapidly induced by microbial stimuli (57). The human TLR3 gene is constitutively and selectively expressed in myeloid DCs, whereas the mouse TLR3 gene is inducible and expressed in macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…54) clarified the species-specific variations of TLR expression in mice and humans. Recent data from several groups suggest that constitutive and inducible TLR expression in different cell types and in different species are controlled by transcriptional regulation (55)(56)(57). Moreover, gene regulatory elements found in the proximal promoters of TLR genes control cell-type specificity and inducible TLR expression in mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…3A and 5B), suggesting a common signalling pathway. Such a pathway may include the central TLR regulator NF-B, which has been shown to play an essential role in the activation of the mouse TLR2 promoter (Musikacharoen et al, 2001;Wang et al, 2001). The mouse TLR4 promoter does not contain NF-B sites but carries several other elements involved in positive (AP-1, Ets, PU.1) and negative (GATA-1 and Oct-1) regulation of TLR4 transcription (Pedchenko et al, 2005;Roger et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been shown that expression of the tlr2 gene is up-regulated after NF-B activation (41,42), we wondered whether the low rate of apoptosis in TLR2-stimulated and MG-132-pretreated cells could necessarily result from the prevention of TLR2 up-regulation by MG-132-mediated NF-B inhibition. Thus, we stimulated peritoneal mouse macrophages prepared from C3H/HeN mice with mouse TNF-␣ (40 ng/ml) for 3 or 16 h, which significantly increases TLR2 expression (43)(44)(45), before treatment with MG-132 and P3CSK4.…”
Section: Tlr4 Potently Signals Agonist-dependent Apoptosismentioning
confidence: 99%